Evaluating the association between DNM1L variants and Parkinson's disease in the Chinese population - Liu, Jiabin; Huang, Juanjuan; Zhao, Yuwen; Pan, Hongxu; Wang, Yige; Liu, Zhenhua; Xu, Qian; Sun, Qiying; Tan, Jieqiong; Yan, Xinxiang; Li, Jinchen; Tang, Beisha; et al. (Frontiers in Neurology, 2023)
Introduction Parkinson's disease (PD) is a progressive movement disorder caused by a loss of dopaminergic neurons. Previous studies have highlighted the importance of mitochondria dynamics in the pathogenesis of PD. Dynamin-1-like (DNM1L) is a gene that encodes dynamin-related protein 1 (DRP1), a GTPase essential for proper mitochondria fission. In the present study, we evaluated the relationship between DNM1L variants and PD in the Chinese population. Methods A total of 3,879 patients with PD and 2,931 healthy controls were recruited and burden genetic analysis combined with high-throughput sequencing was applied. Results We identified 23 rare variants in the coding region of DNM1L, while no difference in variant burden was shown between the cases and controls. We also identified 201 common variants in the coding and flanking regions and found two significant SNPs, namely, rs10844308 and rs143794289 [odds ratio (OR) = 1.220 and 0.718, p = 0.025 and 0.036, respectively]. We also performed a meta-analysis to correlate the two SNPs with PD risk. However, none of the common variants was significant using logistic regression. Conclusion Despite the critical role of DRP1, our study did not support the relationship between DNM1L variants and PD risk in the Chinese population.